Ensaios em política fiscal e monetária brasileira - Faro, Kelly Cardoso (2018)
The objective of this doctoral thesis is to make an empirical study of three important topics in fiscal and monetary policy related to the Brazilian economy in the recent period (1999 to 2018), namely: i) budgetary and fiscal dynamics through the study of triple deficits; ii) use of foreign savings as a policy of economic growth; iii) broad monetary conditions index aggregating government fiscal result. What we seek to analyze empirically are the gaps in the interrelation of these policies and how they react to adverse situations for economic activity as the fiscal question in Brazil has been and if the public deficits generate real impacts in the conduct of the monetary policy. The methodology used in the trials involves the estimation of Autoregressive Distributed Diffusion Models (ARDL), adequate to include a cointegration approach and measurement of short and long term parameters. Regarding the occurrence of triple deficits in the Brazilian economy, the first empirical essay seeks to verify the relationship between fiscal result, current account result (twin deficits) and private savings. The methodology used quarterly data, for the period 2003: 1 to 2016: 4 with the 3 variables cited, and adds as control variables, the GDP, the Selic interest rate and the exchange rate. The empirical results found suggest that there is a long-term relationship between the primary outcome, current account result and national private savings. In relation to short-term dynamics, the mean of the Error Correction Mechanism is 60%. It means that although there is a long-term relationship, it is possible that there are short-term deviations, and that the long-term correction is fast, at an average of 60% in the first quarter. In short, there are clear signs of confirmation of the Triple Deficit Hypothesis for the Brazilian economy. Still in the discussion of consecutive current deficits in the Brazilian economy, we seek to empirically examine whether foreign savings can supply the deficits in Brazilian domestic savings and raise the country's GDP. In the economic literature, the classic view claims to be possible and viable growth with external savings, while a line of critical thinking in this view advocates that the inflow of external resources affects domestic investments only in the short run, when it does, being irrelevant growth in the long run. Based on these two disparate views, the empirical study with quarterly data, for the period 1999: 4 to 2017: 4, seeks to indicate which of the two views most closely approximates the Brazilian reality. The results indicated an approximation to the understanding of the critical view since the estimations indicate that the external saving did not appear statistically significant in the long term in the explanation of the Brazilian economic growth in the selected period. Finally, when analyzing the interrelationship between monetary and fiscal policy, in direct consonance with the theoretical discussion, this measure, we measure a broad Monetary Conditions Index (ICM) for Brazil that presents the current relationship between GDP, the interest rate , the exchange rate and the fiscal result of the government. The study applies the ARDL method to estimate the weights / coefficients of variables in the broad ICM for Brazil in the period 2002: Q4 to 2018: Q1. The result of the index that expands a monetary indicator with a fiscal variable suggests a greater weight of the transmission channel of the interest rate followed by the exchange rate channel and, finally, by the channel of the fiscal result, implication this, which puts in primacy the interest rate channel in determining the level of output in Brazil.